Effects of Matricaria Recutita (L.) in the Treatment of Oral Mucositis - Vânia Thais Silva Gomes; Raimundo Nonato Silva Gomes; Maria Silva Gomes; Walderez Moreira Joaquim; Eliana Campêlo Lago; Renata Amadei Nicolau (The Scientific World Journal)
Objective. The objective of this study was to review the effects of the Matricaria recutita (L.) in the treatment of oral mucositis. Methodology. The online search was performed in the period from June 2016 to April 2018 by means of databases LILACS (Latin American and Caribbean Center on Health Sciences Information), SciELO (Scientific Electronic Library Online), and MEDLINE (Medical Literature Analysis and Retrieval System Online). The consultation was restricted to the years 1991 to 2018 with the aim of elucidating the effects of Matricaria recutita in the treatment of oral mucositis. Results. The final sample consisted of 21 studies, of which 10 were developed in animals and 11 in humans, published from 1991 to 2017, with a total sample of 644 patients. The total number of patients treated with Matricaria included in 11 studies was 364, while in the control groups the total number was 280. In experimental studies, animal models used were rats and the sample size ranged between 36 and 105 animals submitted to the induction of oral mucositis, where 4 studies used an intraperitoneal injection of 5-fluorouracil, while 7 induced lesion in the mucosa. From the data collected, it should be noted that both studies with humans and with animals showed significant effects. In this way, there is strong evidence for the discussion on the therapy; however, it should be noted that more studies are developed in order to clarify the most appropriate protocol for the prevention and treatment of injuries. Conclusion. According to the results found in this study, Matricaria recutita appeared to be a promising alternative for the treatment of oral mucositis. However, due to the great variability in the various types of intervention, more controlled double-blind randomized clinical studies are necessary to ensure the best protocol for treating oral mucositis.